Policy Implementation of Land Value Zone Towards Transaction Value in Assets of Land Office - Rodhita Nur Gustiananda; Amin Purnawan; Akhmad Khisni (Sultan Agung Notary Law Review, 2020)
The purpose of this research is to: 1) To find out what are the regulations governing Land Value Zones in Indonesia, 2) To find out the implementation of the Land Value Zone policy on Transaction Value in deeds at the Kuningan Regency Land Office. The data used in this study are primary materials, secondary materials and testier materials that can support the assessment, which are then analyzed using the empirical juridical method. Based on the results of data analysis, it is concluded that: 1) The regulation regarding Land Value Zones in Indonesia has not yet been specifically regulated regarding the determination of Land Value Zones or land value information, but the community also does not really understand the land values based on or determined by the Land Value Zones In the Kuningan Regency Land Office as well as the Kuningan Regency Regional Regulation, it also does not regulate market value or the Land Value Zone policy which in the end has different policies between agencies. 2) In terms of the legal substance related to the Land Value Zone, Kuningan Regency has not realized it due to clashes between employees regarding the rules.